BOXING SPEED AND MUSCLE SCIENTIFIC TRAINING - Wu,Qingsong (2022)
ABSTRACT Introduction: Boxing is a sport that requires a lot of explosive power, that is, it demands from its practitioners not only to use their strength, but to do so very rapidly. Objective: To analyze the influence of muscle training on the explosive power of boxers, providing a theoretical reference for the training of their core strength. Methods: This article makes a statistical analysis of boxing explosive power and analyzes the factors relevant to punch speed. Results: The key factors that affect the maximum speed of the straight punch in boxing are the maximum elbow joint flexion and extension, angular velocity, and the maximum trunk angular velocity. Conclusion: In daily training, attention should be paid to upper limb strength and core strength training, which is the only way for boxers to have a correct body posture and ensure a reliable center of gravity when punching. Level of evidence II; Therapeutic studies - investigation of treatment results.